The Role of Product Quality and Product Innovation on Competitive Advantage: A Study on Nutrition Clubs in Banjarmasin, Indonesia - Faridatun Nisa; Anisah, Hastin Umi (Open Access Indonesia Journal of Social Sciences, 2023)
Competitive advantage is the ability of a company to produce and provide superior products or services compared to its competitors. One of the important keys to achieving a competitive advantage is through product quality and product innovation. This study aimed to determine the role of product quality and product innovation on competitive advantage, a case study at the Nutrition Club in Banjarmasin, Indonesia. This study was an associative quantitative observational study. A total of 90 research respondents participated in this study, where the respondents were managers of a nutrition club in Banjarmasin, Indonesia. This study observes the variables of product quality (X1), product innovation (X2), and competitive advantage (Y). The analysis technique used in this study is SEM-PLS (structural equation modeling-partial least square) through SmartPLS 4.0 software. Product quality (X1) to competitive advantage (Y) directly, which shows the original sample value (path coefficient) 0.790, T- statistic 9.625, and P-value 0.000, so that the effect of competitive advantage (X1) on competitive advantage (Y) (significant condition for T-statistic > 1.96 and P Value < 0.05 has a positive correlation. Meanwhile, the Product Innovation variable (X2) to competitive advantage (Y) directly shows the original sample value (path coefficient) 0.214, T-statistic 2.604, and P-values 0.009, so the effect of product innovation (X2) on competitive advantage (Y) (significant condition for T-statistic > 1.96 and P-value < 0.05 has a positive correlation. Product quality plays a role in competitive advantage, and product innovation also plays a role in competitive advantage.